Mechanical properties of low-alloyed YSt-355-FR (0.126%Mo) cold-formed steel tube at elevated temperatures. (May 2022) - Kumar, Waibhaw; Sharma, Umesh Kumar; Pathak, Prashant
Abstract: With the advancement in the steel-making process, micro-alloyed steels with small amounts of Nb and Mo, etc., have been developed, which can retain superior strength at higher temperatures. Towards this end, this study investigates a newly developed low-alloyed YSt-355-FR cold-formed steel having Mo content less than 0.15% through the evaluation of the mechanical properties of its hollow steel sections. The standard tension tests on 84 tensile coupons taken from every region (non-welded, welded, and corner) of hollow steel cross-section at steady-state were conducted at temperatures between 20 °C and 800 °C with 120 min holding time. The stress-strain curves were plotted at different temperature levels, and results were discussed in terms of reduction factors of key strength and stiffness properties. The test results show that the location of steel in the tube cross-section has a significant influence on its mechanical properties. The results obtained for the cold-formed YSt-355-FR structural steel suggest the necessary inclusion of proposed new strength reduction factors for the cold-formed steels and up-gradation in the strength reduction factors of hot-rolled steels in the relevant fire design standards. The use of yield strength at 2% strain (upto 500 °C) and at 1% strain (beyond 500 °C) yields optimum buckling strength of YSt-355-FR columns. The provisions mentioned in the EC3 safely predicted the buckling strength of the YSt-355-FR steel tube columns compared to that predicted by the finite element analysis. Important observations have been made in this study, which shall help designers and practitioners in designing steel structures using cold-formed steel tubular sections. Graphical abstract: Unlabelled Image Highlights: Novel YSt-355-FR cold-formed structural steel tube was developed. YSt-355-FR structural steel having 0.126% Mo content by weight. Steady-state tensile test was performed on novel steel at elevated temperature. Mechanical properties and reduction factors were obtained.